Antiallodynic Effects of Cannabinoid Receptor 2 (CB2R) Agonists on Retrovirus Infection-Induced Neuropathic Pain. (4th July 2019) - Sheng, Wen S.; Chauhan, Priyanka; Hu, Shuxian; Prasad, Sujata; Lokensgard, James R.
Abstract : The most common neurological complication in patients receiving successful combination antiretroviral therapy (cART) is peripheral neuropathic pain. Data show that distal symmetric polyneuropathy (DSP) also develops along with murine acquired immunodeficiency syndrome (MAIDS) after infection with the LP-BM5 murine retrovirus mixture. Links between cannabinoid receptor 2 (CB2 R) and peripheral neuropathy have been established in animal models using nerve transection, chemotherapy-induced pain, and various other stimuli. Diverse types of neuropathic pain respond differently to standard drug intervention, and little is currently known regarding the effects of modulation through CB2 Rs. In this study, we evaluated whether treatment with the exogenous synthetic CB2 R agonists JWH015, JWH133, Gp1a, and HU308 controls neuropathic pain and neuroinflammation in animals with chronic retroviral infection. Hind-paw mechanical hypersensitivity in CB2 R agonist-treated versus untreated animals was assessed using the MouseMet electronic von Frey system. Multicolor flow cytometry was used to determine the effects of CB2 R agonists on macrophage activation and T-lymphocyte infiltration into dorsal root ganglia (DRG) and lumbar spinal cord (LSC). Results demonstrated that, following weekly intraperitoneal injections starting at 5 wk p.i., JWH015, JWH133, and Gp1a, but not HU308 (5 mg/kg), significantly ameliorated allodynia when assessed 2 h after ligand injection. However, these same agonists (2x/wk) did not display antiallodynic effects when mechanical sensitivity was assessed 24 h after ligand injection. Infection-induced macrophage activation and T-cell infiltration into the DRG and LSC were observed at 12 wk p.i., but this neuroinflammation was not affected by treatment with any CB2 R agonist. Activation of JAK/STAT3 has been shown to contribute to development of neuropathic pain in the LSC and pretreatment of primary murine microglia (2 h) with JWH015-, JWH133-, or Gp1a-blocked IFN-gamma-induced phosphorylation of STAT1 and STAT3. Taken together, these data show that CB2 R agonists demonstrate acute, but not long-term, antiallodynic effects on retrovirus infection-induced neuropathic pain.